PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 LENGAYANG - Dewi Kaisyah, Defrianti; Aima, Zulfitri; Rahima, Rahima (Pendidikan Matematika, 2014)
ABSTRACTThis research is motivated by the ability of  understanding the concept of mathematical ability of students is still low, and students are not accustomed to discuss. This study aims to determine whether students understanding of mathematical concepts by implementing  cooperative learning Make a better Match than the students understanding of concepts with conventional  learning class VIII SMPN 1 Lengayang. This type of research is experimental research. Sampling Technique is random sampling, which was chosen as the experimental class and the control class VIII 3 is VIII 4. The instrument used in this study is the final test with a reliability study 0, 736. Based on the results of data analysis, the second class of samples are not normally distributed. Data analysis techniques use were Mann-Whitney  test. Hypothesis test results obtained probality = 0,0478. Seen that probality  is  the so the hypothesis of this study is accepted. So, it can be concluded that the students understanding of mathematical concepts by implementing  cooperative learning Make a better Match than understanding of the concept of the convensional learning students in class VIII SMPN 1 Lengayang.